Explica el proceso formación del universo e identifica los elementos que conforman - Valenzuela Mayta, Segundo Gerardo (2018)
On a daily basis we share with our student’s ideas, experiences, occurrences that allow them to learn from their environment and their needs in the area of science and technology. Reality demands literate citizens on these issues, which implies understanding concepts, principles, laws and theories of science, developing scientific skills and attitudes to know the natural world, explain natural phenomena, know how to face or offer alternative solutions to local problems., regional, national or global, climate change, the deterioration of ecosystems, the irrational exploitation of natural resources, diseases and epidemics.